Stent Thrombosis - Mythy and Facts - Yildiz, Mustafa; Sahin Yildiz, Banu; Aydin, Ebuzer; Akin, Ibrahim (Cardiovascular & Haematological Disorders - Drug Targets, 2014)
Stent thrombosis is a serious complication in stent era. It can be presented as death, cardiogenic shock or a large non-fatal myocardial infarction, usually with ST elevation. Risks of stent thrombosis, stent thrombosis incidence and predictors are controversial issues due to sparse and controversial data. But all attending physicians should have knowledge of the risk of stent thrombosis, predisposing and protective factors before and after the intervention. This issue is discussed in detail in this review.
Keywords: Clopidogrel